The utility of the principle of intergenerational equity in strategic climate change litigation in South Africa: lessons from Colombia and Germany - Reinecke, Emma (Department of Public Law, 2024)
Climate change is a threat not only to present generations, but to all present and future inhabitants of the planet as well as the planet itself. Recent climate change litigation has shown a growing trend in utilising the principle of intergenerational equity – the idea that there should be equality between generations, and that present generations owe future generations duties that involve safeguarding and protecting the environment. This minor dissertation analyses the role and utility of the principle of intergenerational equity in strategic climate change litigation with a view to highlighting its potential usefulness in the South African context. It begins by unpacking the theory of intergenerational equity and its differing interpretations. It goes on to consider what strategic climate change litigation is, what the key issues for litigants are, and what successful strategies have been employed in this exciting and rapidly growing area of law. Next, two cases – one from Colombia and one from Germany – in which litigants successfully utilised the principle of intergenerational equity in climate change litigation are analysed. Key lessons are then drawn with particular reference to the different interpretations of intergenerational equity and the main issues in climate change litigation highlighted earlier. Thereafter, the position of the principle of intergenerational equity is considered in the South African context, with a particular focus on the trickier elements of climate change litigation, namely: standing, rights and obligations, and remedies. Finally, the conclusion provides an overarching review and analysis of the principle of intergenerational equity as a strategic climate change litigation tool in South Africa.